Natural regeneration in a restored area of the Tamaulipas thornscrub of Northeast Mexico: - Patiño-Flores, Ana María; Alanís-Rodríguez, Eduardo; Molina-Guerra, Víctor Manuel; Jurado, Enrique; González-Rodríguez, Humberto; Aguirre-Calderón, Oscar; Collantes-Chávez-Costa, Alejandro (Ecosistemas y Recursos Agropecuarios, 2022)
Restoration with native species of the Tamaulipas Thorny Scrub (MET) is being carried out given the high degree of degradation suffered by this ecosystem. In the present study, tall vegetation and regeneration were evaluated in an MET area after 5 years of being restored. Total height, basal diameter and crown diameter were measured for each individual, for which sites of 200 m2 were used for tree and shrub vegetation, and 1 m2 for regeneration. The importance value index (IVI), Margalef (DMg) and Shannon (H’) indices were determined. Diversity was low. The regeneration registered six species of which three were not used in the plantation; Vachellia farnesiana presented higher IVI both in tall vegetation and in regeneration. With the restoration, it has been possible to have mature individuals with the capacity to give way to natural regeneration.